2018
DOI: 10.2337/db17-0490
|View full text |Cite
|
Sign up to set email alerts
|

Production of Elastin-Derived Peptides Contributes to the Development of Nonalcoholic Steatohepatitis

Abstract: Affecting more than 30% of the Western population, nonalcoholic fatty liver disease (NAFLD) is the most common liver disease and can lead to multiple complications, including nonalcoholic steatohepatitis (NASH), cancer, hypertension, and atherosclerosis. Insulin resistance and obesity are described as potential causes of NAFLD. However, we surmised that factors such as extracellular matrix remodeling of large blood vessels, skin, or lungs may also participate in the progression of liver diseases. We studied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…Finally, subjects with hepatic steatosis treated with MK-4074 (liver-specific inhibitor of ACC1 and ACC2) had a 36% reduction in lipid content after 4 weeks of intervention (Kim et al 2017). Thus, therapies that reduced the content levels activity of ACC in the liver were the subject of several studies for the prevention and treatment of NAFLD (Nuñez-Durán et al 2018, Romier et al 2018. In this context, aerobic training is known to provide an increase in the phosphorylation of ACC in the liver of obese animals, inhibiting its lipogenic action (Rector et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, subjects with hepatic steatosis treated with MK-4074 (liver-specific inhibitor of ACC1 and ACC2) had a 36% reduction in lipid content after 4 weeks of intervention (Kim et al 2017). Thus, therapies that reduced the content levels activity of ACC in the liver were the subject of several studies for the prevention and treatment of NAFLD (Nuñez-Durán et al 2018, Romier et al 2018. In this context, aerobic training is known to provide an increase in the phosphorylation of ACC in the liver of obese animals, inhibiting its lipogenic action (Rector et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…CD36 receptor is also modulated by Neu-1, which activates an intracellular signaling cascade that increases the uptake of oxLDL by macrophages, thus, contributing to atherosclerotic plaque formation (50). EDPs have been shown as regulators of insulin resistance development (51), chemotactic attractors to cancer cells (52), and contributors to lipid accumulation in hepatocytes in patients with nonalcoholic steatohepatitis (NASH) (53). It has been demonstrated that, besides physiological aging, several genetic alterations also lead to connective tissue disorders related to elastin degradation.…”
Section: The Physiological Function Of Elastinmentioning
confidence: 99%
“…The first model was composed of six proteins (fibrinogen β chain, retinol binding protein 4, serum amyloid P component, lumican, transgelin 2, and CD5 antigen-like), and the second involved three proteins (component C7, insulin-like growth factor acid labile subunit, and transgelin 2); the AUROC values ranged from 0.83–0.91 for different stages of NAFLD [158]. Due to multiomic studies, numerous biomarkers have been revealed to be associated with NAFLD, as they are involved in necroinflammation and fibrogenesis [159,160,161,162,163,164,165].…”
Section: Genetical Evaluation and Multi-omics Profiles Of Nafldmentioning
confidence: 99%